2021
DOI: 10.1093/eurjpc/zwab185
|View full text |Cite
|
Sign up to set email alerts
|

A resilient type of familial hypercholesterolaemia: case–control follow-up of genetically characterized older patients in the SAFEHEART cohort

Abstract: Aims  Knowledge of the features of patients with familial hypercholesterolaemia (FH) who are protected from atherosclerotic cardiovascular disease (ASCVD) is important for the clinical and prognostic care of this apparently high-risk condition. Our aim was to investigate the determinant and characteristics of patients with FH who are protected from ASCVD and have normal life expectancy, so-called ‘resilient’ FH (R-FH). Methods and results  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…As previously detailed, resilient HeFH subjects of the present study were younger, mostly female, presented fewer comorbidities, and had higher HDL and lower Lp(a) concentrations at baseline in comparison to the ACVD group. These results fully agree with those observed in the SAFEHEART study in genetically defined patients ≥ 65 years old with HeFH diagnosis in Spain [11]. In that study [11], the resilient group profile also englobed those subjects with a younger age, female gender, absence of hypertension, elevated HDL cholesterol and decreased Lp(a) levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As previously detailed, resilient HeFH subjects of the present study were younger, mostly female, presented fewer comorbidities, and had higher HDL and lower Lp(a) concentrations at baseline in comparison to the ACVD group. These results fully agree with those observed in the SAFEHEART study in genetically defined patients ≥ 65 years old with HeFH diagnosis in Spain [11]. In that study [11], the resilient group profile also englobed those subjects with a younger age, female gender, absence of hypertension, elevated HDL cholesterol and decreased Lp(a) levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, the possible associated factors to the cardiovascular-event free survival in these individuals have not been fully established. In this regard, a recent study [11] with HeFH subjects aged ≥ 65 years, observed that factors such as age, gender, carrying a defective mutation, presence of comorbidities and lipid subfractions were related to the presence or not of ACVD. However, further evidence on whether this resilience state is maintained over time, or if these same factors apply for resilient HeFH subjects of a more advanced age, is, at present, very scarce and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, this same group published the determinants and characteristics of patients with FH who were protected against ASCVD and had a normal life expectancy, the so-called “resilient” FH. Being female, having a defective LDL receptor mutation, higher plasma HDL-C levels, lower Lp(a) levels, and absence of hypertension were associated with this condition [14 ▪▪ ].…”
Section: Need To Estimate the Risk In Individuals With Familial Hyper...mentioning
confidence: 98%
“…Risk stratification can identify patients who require treatment intensification and guide the best use of healthcare resources [13]. Male gender, late initiation of LLT, smoking, low high-density lipoprotein cholesterol (HDL-C), obesity, DM, hypertension, chronic kidney disease, and elevated lipoprotein(a) [Lp(a)] levels are independent predictors of the risk of ASCVD in patients with FH [14 ▪▪ ,15]. There is a clear need for improved assessment of sex-specific risk factors for ASCVD in women with FH, such as reproductive history.…”
Section: Need To Estimate the Risk In Individuals With Familial Hyper...mentioning
confidence: 99%
“…It follows that extremely elevated Lp(a) concentrations (>95 percentiles, 100 mg/dL or 200 nmol/L) would be strongly predictive of future ASCVD in FH. Conversely, low Lp(a) levels (1–74th percentile, 0–30 mg/dL or 0–60 nmol/L) may contribute to resilience against ASCVD in FH ( Perez de Isla et al, 2021 ).…”
Section: Double-trouble: Fh and Hyper-lp(a) As Dual Risk Factorsmentioning
confidence: 99%